2010
DOI: 10.1051/0004-6361/201014506
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared and optical observations of galactic warps: a common, unexplained feature of most discs

Abstract: Context. Warps occurring in galactic discs have been studied extensively in HI and in the optical, but rarely in the near-infrared (NIR) bands that trace the older stellar populations. Aims. We provide NIR data of nearby edge-on galaxies, combined with optical observations, for direct comparison of the properties of galactic warps as a function of wavelength, and calculate warp curves for each galaxy and obtain the characteristic warp parameters. We discuss these properties as possible constraints to the diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The Galactic warp has since been seen in the dust and stars (Freudenreich et al 1994;Drimmel & Spergel 2001;López-Corredoira et al 2002;Momany et al 2006;Marshall et al 2006;Robin et al 2008;Reylé et al 2009). Our Galaxy is not peculiar with respect to other disk galaxies: more than 50 percent of spiral galaxies are warped (Sanchez-Saavedra et al 1990;Reshetnikov & Combes 1998;Guijarro et al 2010). The high occurrence of warps, even in isolated galaxies, implies that either these features are easily and continuously generated, or that they are stable over long periods of time.…”
Section: Introductionmentioning
confidence: 84%
“…The Galactic warp has since been seen in the dust and stars (Freudenreich et al 1994;Drimmel & Spergel 2001;López-Corredoira et al 2002;Momany et al 2006;Marshall et al 2006;Robin et al 2008;Reylé et al 2009). Our Galaxy is not peculiar with respect to other disk galaxies: more than 50 percent of spiral galaxies are warped (Sanchez-Saavedra et al 1990;Reshetnikov & Combes 1998;Guijarro et al 2010). The high occurrence of warps, even in isolated galaxies, implies that either these features are easily and continuously generated, or that they are stable over long periods of time.…”
Section: Introductionmentioning
confidence: 84%
“…For instance, deep optical surveys of nearby face-on and edge-on dIrrs and disk galaxies have also found that their stellar distributions are much more extended than previously thought, e.g., NGC 6822 (de Blok & Walter 2006), Leo A (Vansevičius et al 2004), IC 1613 (Battinelli et al 2007), Pegasus (Kniazev et al 2009), the Magellanic Clouds (Casetti-Dinescu et al 2012, and references therein) and the works of Malin & Hadley (1999); Tikhonov (2005Tikhonov ( , 2006. Moreover, warps and flaring have been shown to be common features of galactic disks (e.g., Guijarro et al 2010; van der Kruit & Freeman 2011, and references therein). In addition, accretion features are now commonly detected (e.g., Martínez-Delgado et al 2008, 2009Mouhcine et al 2010;Miskolczi et al 2011;Ludwig et al 2012).…”
Section: A Minor Axis Density Profile For M31mentioning
confidence: 91%
“…By utilizing radial velocities and proper motions from outside catalogs, one would be able to trace the structure and kinematics of the disk as a function of position in the Galaxy, especially in the following respects: (1) The depth of LAMOST will allow the 3-D structure of the northern Galactic warp (Guijarro et al 2010) in the Galaxy to be traced, using giants and red clump stars in distant clusters ; (2) Kinematic data of OCs will also allow us to systematically study the Galactocentric rotation velocity, which will provide definitive estimates of the mass of the Galaxy, and also the principal scale parameter − the distance of the Sun from the Galactic center, R ⊙ ; and (3) By combining chemical abundances and ages of OCs, one will be able to probe the correlations between age, velocity, and abundance as a function of position in the Galaxy (Yu et al 2012).…”
Section: Open Clustersmentioning
confidence: 99%